Magic-ritual functions of the musical culture of the Altai people - T. M. Sadalova (Nomadic Civilization: Historical Research)
The unique musical culture of the Altai people is largely based on traditional folk music. National musical instruments have sacred, magical functions when communicating with the spirits of nature — this fact is reflected in folklore works and folk performances. The article attempts to comprehensively clarify the relationship of the sacred, magical functions of folk musical instruments with a variety of cult rituals that exist in the life of Altai society, with established stereotypes in the texts of oral folk art, as well as in oral stories of representatives of the ethnic group. One of the oldest samples of musical instruments found by archaeologists, the Pazyryk harp, is considered in detail. The scientific study of this unique artifact, as it seems to us, will help to expand our understanding of its existence in the past, to understand the main substantive components of the “Scythian harp” in order to preserve them during reconstruction and revive the ancient musical instrument for the modern generation of musicians and listeners.The study of the national musical instrument, the Pazyryk harp, as one of the most valuable sources of the historical and cultural heritage of the Altai people is very relevant and is of scientific interest to Russian and foreign experts, folklorists, archaeologists, culturologists and modern musicians.